Port of Spain, Trinidad - (:unkn) unknown (Unknown, 2011)
The postcard shows sailors walking among civilians near the St. Vincent Jetty in Port of Spain, Trinidad. Horse drawn carriages and automobiles can also be seen.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Harbors--Trinidad and Tobago; Jetties--Trinidad and Tobago; Sailors--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Uniforms--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Transportation--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Ships--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Barrels--Trinidad and Tobago; [1915]